Utilization of AI to Predict Shear Strength Parameters of Soil Based on Their Physical Properties - AbdulGhafour, Husaen (2025)
A Master of Science thesis in Civil Engineering by Husaen AbdulGhafour entitled, “Utilization of AI to Predict Shear Strength Parameters of Soil Based on Their Physical Properties”, submitted in November 2025. Thesis advisor is Dr. Mousa Attom. Soft copy is available (Thesis, Completion Certificate, Approval Signatures, and AUS Archives Consent Form).